THE PERSONALITY OF ESTHER COLEMAN IN JAUME COLLET SERRA'S ORPHAN MOVIE (2009): A PSYCHOANALYTIC APPROACH - PRIHATIN, PAPANG (2011)
The research is proposed to analyze the personality of Esther in a film entitled Orphan using a Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural element, and the second is to analyze the film based on Psychoanalytic Approach. The type of the research is qualitative. The primary data source used by the writer is Orphan movie and this script is written by Alex Mace. Movie script is taken from website. The secondary data are taken from the other sources which relate to this movie such as biography of the author and the other relevant information. The method of collecting data is library research whereas the technique for analyzing is descriptive analysis. In this study, the writer draws two conclusions as follows: first, in Orphan through the kinds of the structural analysis, it can be seen that the structural elements of the film has contribution in creating the film. It also supports each other because the theme, character and characterization, plot, mise_en_scene, sound, editing comprehensively build unified structure and give contribution to the total meaning of work. Secondly, Orphan is a story charged with ambition and emotion, in which the integrity of being human meets a terrifying test. Jaume Collet Serra's stunning film explores what happens when a little girl is falling in love with her father, and trouble in Coleman's family.